2003
DOI: 10.1046/j.1469-0691.2003.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular tuberculosis in a general hospital during the last decade

Abstract: A high degree of suspicion is still needed to avoid a delayed diagnosis that might complicate the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
2
29
1
2
Order By: Relevance
“…In our study a slight male predominance was seen. Clinically, pain is the commonest symptom, as encountered in our series [11,15]. Local swelling and sinuses can be seen in some cases [2]; one of our cases showed multiple sinuses.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In our study a slight male predominance was seen. Clinically, pain is the commonest symptom, as encountered in our series [11,15]. Local swelling and sinuses can be seen in some cases [2]; one of our cases showed multiple sinuses.…”
Section: Discussionmentioning
confidence: 65%
“…Studies in different countries (Romania, Spain, Israel and Korea) have found 19, 26, 38 and 41 cases respectively, over a span of 10 years [8,9,12,15]. However, in a study at a busy teaching institute in Thailand, 99 cases of osteoarticular TB were found from the electronic data base during a 2 year period, which appears to be a very significant number of cases [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…India accounts for nearly 20% of the total TB burden [2]. Of these, nearly 1-5% of cases have skeletal TB [3][4][5][6]. As TB is endemic in India, most orthopedic surgeons diagnose osteoarticular TB based on clinical and imaging findings only and initiate empirical anti-TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 20 pus swab specimens which were negative by conventional staining and culture methods, PCR detected 4 positive cases (20%) of musculoskeletal tuberculosis. The findings related to poor yield of pus was also reported in the study conducted by Ganavalli et al 14 (25.8%) and Maurya et al 21 (27.65%), However, these findings were inconsistent from the study of Ruiz et al 11 (66.67%) and Prakash et al 13 (43.24%). In the study 14 USG guided pus aspirate samples were collected from suspected musculoskeletal tuberculosis patients, among them 1 (7%) was positive on smear microscopy and 6 (42.9%) were positive on LJ culture medium, however, PCR demonstrated 10 positive (71.4%) samples.…”
Section: Discussionmentioning
confidence: 73%